African delegation tells Putin 'war must' end, Russia says 'open to dialogue' - News Wires (France 24, 2023)
A delegation of African leaders including South African President Cyril Ramaphosa met with Russian President Vladimir Putin in Saint Petersburg on Saturday as part of its mission to try to broker peace talks between Moscow and Kyiv. The meeting comes a day after the delegation met with Ukrainian President Volodymyr Zelensky, and as Putin confirmed that he has deployed tactical nuclear weapons to Belarus. Read our live blog to see how all the day's events unfolded.
Africa
Keywords: 2023-06 June